On One Class of Divisors of Polynomial Matrices over Integral Domains - Prokip, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We establish conditions for the existence of a unital divisor for a polynomial matrix over an integral domain of characteristic zero in the case where its eigenvalues are known.